J.H. Johnston, Revised Charter and Ordinances of the City of Boonville, Missouri 44 (1881) - (:unkn) unknown (My University, 1881)
Art. 11, § 13: regulate the storage of gun powder and other combustible materials; and generally provide for the prevention of fires within the city.
Keywords: GUNPOWDER - STORAGE